A saccharide-based binder for efficient polysulfide regulations in Li-S batteries - Yingyi Huang (Nature Portfolio, 2021)
The long-term cycling of Li-S batteries depends on the polysulfides shuttling regulation. Here, the authors present a saccharide-based binder system to control the polysulfides migration and improve the cycle life of a Li-S pouch cell.